“What’s the point, when we’re already dead?” Implementation challenges of COVID-19 public policies for indigenous peoples in the Peruvian Amazon: A sequential multi-method qualitative study - Andrea Valdivia-Gago; Patricia J. García; Sherilee L. Harper; Angela Soria; Carol Zavaleta-Cortijo (PLoS ONE, 2026)
Peru issued multiple COVID-19 policies for the Amazon, yet how they worked in practice for Indigenous Peoples remains under-documented. We conducted a sequential multi-method qualitative study, reviewing 20 national and regional policy documents (Mar–Dec 2020) and interviewing 12 implementers, regional and local officials from the health sector (n = 8) and the Ministry of Culture (n = 4), plus one central-level culture representative, in Loreto and Junin. Triangulating top-down policy review with bottom-up practitioner accounts across two contrasting regions strengthened validity. Policies frequently lacked explicit intercultural guidance, clear monitoring indicators, and dedicated budgets. Implementers described budget misalignment, omission of specific health networks, delayed supplies, and connectivity barriers that fostered dissatisfaction and a perception that services prioritized data collection over care. Effects were most acute in remote and low-connectivity settings; Indigenous federations’ participation in Loreto sometimes mitigated challenges, while in Junin travel-fund constraints limited participation. Pandemic preparedness must institutionalize intercultural approaches and secure sustainable funding with clear accountability. Co-design with Indigenous organizations, ring-fenced implementation budgets, practical communication strategies, and routine monitoring are essential to protect Indigenous Peoples in future health emergencies.